Szlachcic, rycerz, baron, hrabia, książę. Badania nad XVI-XVIII-wieczną szlachtą południowej części województwa lubuskiego = Nobleman, knight, baron, count, duke: research on the 16th/17th century nobility of the southern part of the Lubuskie Voivodeship - Kuczer, Jarosław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of this article is to present the achievements of the historical community at the Institute of History, University of Zielona Gora, regarding the research on the nobility of the Silesian-Greater Poland-Lusatian-Brandenburg borderland from the 15th to the 19th century. This research has been ongoing since 1999, initiated and overseen by Kazimierz Bartkiewicz and Wojciech Strzyżewski within the Department of General and Polish History of the 16th-18th Centuries.
Keywords: rycerz; szlachcic; baron; hrabia; książę; Ziemia Lubuska; nobleman; knight; count; duke; Lubuskie Region